The COVID-19 Anxiety, Depression and Stress Levels of AIMS Students and their Impact on Well-Being: Inputs for Mental Resiliency Program - Jasmin, Patricia; Garibay, Marianne; Adesna, Marjorie C.; Makilang, Diane M.; Pangilinan, Jo Anne E. (Future Science / FSH-PH Publications, 2023)
The COVID-19 pandemic brought uncertainties and complexities to both national and global societies, impacting various sectors, including education. This study focuses on the effects of pandemic-related challenges on students' achievement and mental well-being at the Asian Institute of Maritime Students (AIMS). The closure of schools and the rapid shift to online learning during lockdowns disrupted students' achievement and mental health. This research aimed to assess the levels of COVID-19-related anxiety, depression, and stress among AIMS students and their subsequent impact on overall well-being. Using a descriptive-correlation research design, data on anxiety, depression, stress, and well-being were collected from a sample of 369 AIMS students through stratified random sampling. The Depression, Anxiety, and Stress Scale (DASS-21) by Lovibond and Lovibond (1995) measured mental health, while the Well-Being Checklist by Loomans (2018) assessed overall well-being. Results indicate that AIMS students experienced mild stress (M= 17.31) and moderate depression (M= 16.78), with notably severe levels of anxiety (M= 15.67). Their overall well-being ranged from moderate to high, encompassing physical, emotional, mental, and spiritual dimensions, resulting in an overall well-being score of 6.95 (moderate). Notably, depression exhibited a significant inverse correlation with overall well-being, while anxiety and stress also showed significant relationships when considered separately. The findings emphasize the need for targeted interventions to enhance students' mental resilience. Programs addressing depression were recommended, given its potential long-term negative impact on students' well-being. These insights contribute to the development of a comprehensive mental resiliency program, vital for promoting the holistic welfare of AIMS student.